THE FORMATION OF STUDENTS' SKILLS FOR PURPOSEFUL INTERNET USE AS A PSYCHOLOGICAL ISSUE - Nabi Mirzaali ogli Sharopov (Western European Studies, 2025)
This article explores students' internet usage in the digital age as a psychological issue. Factors such as internet addiction, aimless time consumption, distractions, and emotional decline are considered negative outcomes of improper internet use. From this perspective, the article analyzes the theoretical foundations, psychological mechanisms, and practical methods for developing students' skills for purposeful internet use
Keywords: internet; digital literacy; psychological problem